2008
DOI: 10.1002/jez.482
|View full text |Cite
|
Sign up to set email alerts
|

The role of prolactin in the regulation of brood care in the cooperatively breeding fish Neolamprologus pulcher

Abstract: The hormone prolactin (PRL) is important for the regulation of parental care in many species of mammals, birds and fish, and for alloparental care (care directed at nondescendant young) in some mammals and birds. Its significance in alloparental brood care of cooperatively breeding fish has not yet been assessed. Here, we test the role of PRL in brood care behavior of the cooperatively breeding cichlid Neolamprologus pulcher. The expression of PRL mRNA was determined in the pituitary glands of breeders of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Therefore, the male bias in expression may be consistent with the observation that in fish prolactin is particularly important for paternal rather than maternal care (Schradin and Anzenberger, 1999). The bias in prolactin expression in our present study of monogamous species is inconsistent with findings from a related cooperative breeding cichlid species (Bender et al, 2008).…”
Section: Sex-biased Gene Expressionsupporting
confidence: 73%
“…Therefore, the male bias in expression may be consistent with the observation that in fish prolactin is particularly important for paternal rather than maternal care (Schradin and Anzenberger, 1999). The bias in prolactin expression in our present study of monogamous species is inconsistent with findings from a related cooperative breeding cichlid species (Bender et al, 2008).…”
Section: Sex-biased Gene Expressionsupporting
confidence: 73%
“…In an accompanying study we found no evidence for a positive effect of prolactin on parental or alloparental care in N. pulcher [36]. Furthermore, several studies showed similar androgen levels in male breeders and male helpers of N. pulcher [5,37], which probably relates to the fact that in this species male helpers may participate in reproduction [38,39].…”
Section: Introductionmentioning
confidence: 55%
“…In this species, PRL does not appear to be important for nest maintenance, and females providing brood care have lower PRL mRNA levels than non-brooding females [8]. As this study used both observational and manipulative experiments and a highly sensitive quantitative real-time PCR (qPCR) assay (see Section 5.3), its counterintuitive results appear to be robust, and may be explained by the fact that N. pulcher is a cooperatively brooding species with a complex social hierarchy.…”
Section: Other Parental Care Behavioursmentioning
confidence: 88%
“…This approach was taken by Bender et al [8] in their study of parental behaviour in the daffodil cichlid (described in Section 4.3.4). This two-pronged tactic provides an increased degree of sensitivity to identify subtle variation in endocrine function and adds greater confidence to experimental results.…”
Section: Recommendationsmentioning
confidence: 99%